Hepatitis C and HCV - Lemon, Stanley (Henry Stewart Talks, 2007)
The spectrum of hepatitis viruses, Global distribution of HCV infection, Associated diseases, Hepatitis C pathogenesis, HCV model systems, Replication of HCV RNA, Hypothetical membrane topology of HCV proteins, HCV structural proteins, p7 protein, Hepatitis C virus life cycle, Polyprotein functions in the viral life cycle, Subgenomic HCV replicon life cycle, The central issue in hepatitis C is viral persistence, Possible mechanisms of HCV persistence
Archived at 2020/08/31